Cost analysis of ureteroscopy (URS) vs extracorporeal shockwave lithotripsy (ESWL) in the management of ureteric stones <10 mm in adults: a UK perspective. (2nd December 2019) - Constanti, Margaret; Calvert, Robert C.; Thomas, Kay; Dickinson, Andrew; Carlisle, Sophie
Abstract : Objectives: To compare the total cost of a treatment strategy starting with ureteroscopy (URS) vs a strategy starting with extracorporeal shockwave lithotripsy (ESWL). Methods: For ureteric stones of <10 mm, URS or ESWL are the main treatment options that are considered. Although the interventions differ, the goal of the interventions is to achieve a stone‐free status. A systematic review and meta‐analysis undertaken as part of the National Institute for Health and Care Excellence (NICE) guideline on 'Renal and ureteric stones: assessment and management' identified URS as more effective, in terms of getting people stone free, but has a higher probability of re‐admission and adverse events (AEs) that contributes to downstream resource use. ESWL is initially less costly, but lower effectiveness means a greater need for repeat or ancillary procedures in order to get a patient stone free. Given these trade‐offs between benefits and costs, a cost analysis of URS and ESWL was undertaken as part of the NICE guideline, using evidence from the literature of effectiveness, re‐admission and AEs. The NICE guideline meta‐analysis showed a lot of heterogeneity and differences in how outcomes were reported between studies. The costing analysis, therefore only used studies where: (i) patients were rendered stone free, and (ii) where effectiveness, was based on the first‐line (initial) procedures. Exploratory quality adjusted life year (QALY) work was also undertaken to identify the QALY and quality of life (QoL) differences required for the most expensive intervention to be cost effective, based on the assumption that the difference in effectiveness between the initial procedures would be the main source of the QALY gain between the two strategies. Results: The URS strategy was more costly overall than the ESWL strategy (incremental cost of £2387 [pounds sterling]). Sensitivity analysis varying the initial effectiveness of ESWL treatment (between the base case value of 82% and 40%) showed that URS would still be a more costly strategy even if the initial session of ESWL only had a success probability of 40%. A two‐way sensitivity analysis as part of the exploratory QALY work showed that ESWL would have to have very low effectiveness and people would have to wait for further treatment for many weeks (following a failed ESWL treatment) for there to be feasible QoL gains to justify the additional cost of the URS strategy. Conclusions: ESWL is less effective at initial stone clearance and therefore requires more ancillary interventions than URS. However, the magnitude of the difference in costs means URS is unlikely to be cost effective intervention at a population level for first‐line treatment, implying ESWL should be the first choice treatment.